Prinsip Qoulan Maysuro dalam Ceramah Gus Iqdam Perspektif Tfsir Asyarowi - Firdaus, Salsabil Fadilah; Pinanditha, Senja Elling; Qolbiyah, Syifaul; Islam, Muhammad Syamsuddinil; Aziz, Moh Ali; Yaqin, Ainul (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2025)
This research examines the principles of qaulan maysura in Gus Iqdam's lectures through the Tafsir Asy-Sya'rawi approach, with a focus on its relevance and application in contemporary da'wah. Qaulan maysura or "gentle words" is a communication ethic recommended in the Koran, which emphasizes the importance of gentleness, friendliness and ease in conveying religious messages. The research method used is content analysis, with a focus on Gus Iqdam's lecture videos on YouTube as the main source, supplemented with references from various sources of commentary and da'wah literature. Through analysis of Tafsir Asy-Sya'rawi, this article explains the concept of qaulan maysura and how this tafsir enriches understanding of empathetic and effective da'wah communication. Gus Iqdam's lecture was chosen as a case study because his communication style reflects the values of qaulan maysura, making him a representative example. The results of this research emphasize the importance of the principles of polite communication in da'wah and show the relevance of Tafsir Asy-Sya'rawi in explaining these values, which are useful for preachers in various social contexts.